Global Supply Chain Management: Challenges and Solution - Rajah, Neerosha; Musa, Haslinda; Nipis, Victor; Kunjee Krishnan, Prasad; Suppiah, Sujitra; Fyrdaus Norull Ahmad, Amir (International Journal of Engineering and Technology, 2018)
Efficient supply chain management is crucial for survival and success in a turbulent world. Current economic crisis increases its importance even further. This conceptual paper reviews latest findings in the most relevant areas of supply chain management. The objective of this paper is to identify global supply chain management challenges and its solutions. In order to achieve the objectives, a thorough literature review was conducted; main findings are reviewed. This review has covered Indian industry, HaiHaâ€™s supplier, and other global perspectives. Therefore, the challenges might be different according to the origin countries and industries. Besides, it is also found that the challenges can be mitigated with some alternatives derived from reviewing the case studies. The findings shown that in order to compete with global participation, efforts on seeking out the solutions would be much encouraged and embedded into the organizations.Â Â Â